LOW-CYCLE FATIGUE LIFE PREDICTION FOR 316 L STAINLESS STEEL USING STRAIN-BASED MODEL - GAN Lei; WU Hao; ZHONG Zheng (Jixie qiangdu)
A series of multiaxial low-cycle fatigue texts were conducted on 316 L stainless steel. Additional hardening was clearly observed under non-proportional loading. Then four strain-based models were utilized for life prediction. The result show that the ASME model and Itoh model could not properly reflect the effect of non-proportional hardening on fatigue life,the ASME model tended to overestimate fatigue life,while the Itoh model contrary to ASME model. Fatemi-Socie model and Susmel model,which both based on critical plane approach,presented better prediction results. In order to overcome the deficiency of ASME model,a practical life prediction model for multiaxial low-cycle fatigue is proposed by means of modifying the plastic term of ASME equivalent strain. Evaluated by utilizing experimental data of six materials including 316 L stainless steel,the proposed model have a higher accuracy than similar models established through modifying ASME model.